Evaluation of stingless bee honey quality (Tetragonula laeviceps) based on their physicochemical from different origins (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Agussalim, Sabir A, Sahlan M, Agus A. 2023. Evaluation of stingless bee honey quality (Tetragonula laeviceps) based on their physicochemical from different origins. Biodiversitas 24: 2134-2142. Honey is a natural food mainly composed of sugars and other components such as enzymes, amino acids, organic acids, carotenoids, vitamins, minerals, and aromatic substances. This study aimed to determine the quality of stingless bee honey (Tetragonula laeviceps) based on their physicochemical from different origins of Lombok, Magelang, and Purworejo (Indonesia). The honey was physicochemically analyzed on its moisture, fat, protein (by proximate analysis), energy (bomb calory meter), flavonoid, phenolic, and DPPH antioxidant (spectrophotometer Uv-Vis), organic and amino acids (high-performance liquid chromatography). Honey from Lombok was lower in moisture content (p
Keywords: Amino acids, antioxidant activity, honey, nectar, organic acids